2020
DOI: 10.1039/d0ra06727j
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical characterization, and antioxidant and antimicrobial activities of white cabbage extract on the quality and shelf life of raw beef during refrigerated storage

Abstract: Brassica vegetables are well-characterized, containing a wide-spectrum of phenolic compounds that are responsible for their diverse biological activities like antioxidant and antimicrobial activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Considering that BCWE has high phenolic content and antioxidant capacity, it can be used as a natural antioxidant to control lipid oxidation in ground beef instead of synthetic antioxidants. The results obtained in the present study are similar to many studies showing that natural antioxidants such as plants, fruits and vegetables delay the oxidative deterioration in fresh meat and meat products 5–8,13–15,31–33,40 . In this regard, Ekici et al 41 demonstrated that black carrot concentrate (BCC) increased the antiradical activities and total phenolic content of Turkish dry‐fermented sausage samples.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Considering that BCWE has high phenolic content and antioxidant capacity, it can be used as a natural antioxidant to control lipid oxidation in ground beef instead of synthetic antioxidants. The results obtained in the present study are similar to many studies showing that natural antioxidants such as plants, fruits and vegetables delay the oxidative deterioration in fresh meat and meat products 5–8,13–15,31–33,40 . In this regard, Ekici et al 41 demonstrated that black carrot concentrate (BCC) increased the antiradical activities and total phenolic content of Turkish dry‐fermented sausage samples.…”
Section: Resultssupporting
confidence: 90%
“…Consistent with our findings, Turan and Şimşek 14 reported that the pH values of beef patties treated with black mulberry extract were lower than the control during 15 days of chilled storage in both aerobic and vacuum conditions. Similarly, a dose‐dependent decrease in pH values of fresh meat products incorporated with various vegetable extracts has been reported in previous studies 31–33 …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The study performed by Rubab et al [59] on white cabbage extracts in 2020 showed that they induced medium to low in vitro activity against all tested microorganisms, with higher activity against Gram-positive bacteria, compared with Gram-negative bacteria. Moreover, the extracts reduced the growth of several fungi strains (including C. albicans), but with lower activity compared with the one on the bacterial strains.…”
Section: Discussionmentioning
confidence: 96%
“…PPs are produced from primary metabolites and intermediates through unique biosynthetic pathways [ 1 ]. They are a class of non-essential phytonutrients and are abundant in fruits, cereals, and vegetables [ 2 , 3 ]. Molecules of PPs display at least one aromatic ring carrying one or more hydroxyl groups [ 4 ] and they are also found as conjugate with organic acids or sugars or as polymers (flavonoids).…”
Section: Introductionmentioning
confidence: 99%